The Study of Effectiveness of Chitosan from Pearl Oyster (Pinctada maxima) Shell as Antibacterial in Bone Scaffold Application - Alaydrus, Mukaddam; Purnaning, Dyah; Ansyori, Maz Isa; Septiani, Nonik; Alawiyah, Geby; Rahayu, Susi; Taufik, Ahmad (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Chitosan is a functional material with potential for bone scaffolds due to its antibacterial properties, biocompatibility, biodegradability, low toxicity, and ability to support tissue regeneration and prevent infections in graft implantation.This study aims to identify changes in functional groups in each isolation process and identify the effect of chitosan concentration on the activity of Straphylococcus aureus and Escherichia coli bacteria. Chitosan isolation methods are demineralization, deproteination, decolorization, and deacetylation by microwave irradiation. Analysis of chitosan functional groups using FTIR, while antibacterial activity test using diffusion method. Isolation of chitosan from pearl oyster shells (Pinctada maxima sp.) obtained a degree of deacetylation of chitosan of 95.37%. Pearl oyster shell powder identified typical peaks of calcium carbonate (CaCO₃). The demineralized powder sample had calcium carbonate (CO₃²⁻) peaks that disappeared. Furthermore, the deproteinated powder sample produced peaks with amide groups (C=O dan N-H) of reduced protein. Decolorized powder samples did not show drastic changes in the bands of the deproteinated powder spectra, but the spectra could show cleaner and clearer peaks without any interference from pigments. The last, deacetylated powder sample showed a decrease in peak intensity in the 1650 cm⁻¹ (C=O amide). The analysis of the ability of chitosan to inhibit the growth of E. Coli and S. Aureus bacteria was effective at a minimum chitosan concentration of 20%. In comparison, antibacterial activity in S. aureus is better than in E. coli. Chitosan from this shell can serve as an antibacterial, but its manufacturing techniques need optimization for better efficacy.